Validation of the brief international cognitive assessment for multiple sclerosis (BICAMS) in the Portuguese population with multiple sclerosis - Sousa, C. (2018)
Background: The validation of international cognitive batteries in different multiple sclerosis (MS) populations is essential. Our objective was to obtain normative data for the Portuguese population of the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) and assess its reliability. Methods: The BICAMS was applied to 105 MS patients and 60 age, gender and education matched healthy controls (HC). In order to test its reliability, BICAMS was re-administered in a subset of 25 patients after a 7-month interval. Results: Most participants were women, with a mean age of 37, 21 years and a mean of 14,08 years of education. The vast majority of the MS patients (92.4%) had the relapsing remitting type, 58.1% were professionally active, mean disease duration was 6.52 years, median EDSS score was 1.5 (range: 0–6.0) and the median MSSS score was 2.01 (IQR range: 3.83). The MS group presented significantly higher scores of anxiety and depression than HC and 47,4% had fatigue. The MS group performed significantly worse than the control group across the three neuropsychological tests, yielding the following values: SDMT: t(165) = 3.77, p = .000; CVLT-II: t(165) = 2.98, p = .003; and BVMT-R: t(165) = 2.94, p = .004. The mean raw scores for Portuguese normative data were as follows: SDMT: 58.68 ± 10.02; CVLT-II: 60.47 ± 10.12; and BVMT-R: 24.68 ± 5.52. Finally, test–retest reliability coefficients for each test were as follows: SDMT: r = .90; CVLT-II: r = .71; and BVMT-R: r = .84. Conclusions: The Portuguese version of BICAMS here in described is a reliable monitoring instrument for identifying MS patients with cognitive impairment.